Optimalisasi Peran Fisioterapi Pada Hipertensi Di Puskesmas Sibela Mojosongo - Syarif Hidayat; Suryo Saputro Perdana; Anisa Dwi Charisa; Haryanti Kartini Mulyaningrum (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction: Hypertension, also known as essential or primary hypertension, has unknown causes. However, there are also cases of hypertension caused by other diseases known as secondary hypertension. Method: The method used is health education related to hypertension and home-based education on hypertension exercises at the elderly community center in Rw 14, Mojosongo Village. Objective: This program aims to increase knowledge and understanding of the definition, factors, and prevention of hypertension by engaging in physical activities such as hypertension exercises specifically tailored for the old adult and in appropriate doses. Results: The result of this health education activity is an increased understanding among old adults about the definition, factors, and prevention of hypertension, as well as the importance of engaging in physical activities. Recommendation: A structured follow-up of this community service activity is needed so that the community can adhere to a healthy lifestyle, thereby reducing complaints and the incidence of hypertension-related diseases.